Composition for welding ceramic and metal as well as preparation method and application of composition
By combining glass powder with organic carriers with components such as tin oxide, phosphorus pentoxide, zinc oxide, lanthanum oxide and other components, ceramic and metal welding compositions were prepared, and the defects of traditional glass seals were solved in harsh environments, achieving high welding strength, stable interface and good acid and alkali resistance.
Patent Information
- Application Number
- CN202411897120.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Traditional glass seals are easily dissolved by alkali metal ions in harsh chemical environments, and the thermal expansion coefficient is difficult to accurately control, and the mechanical strength is limited by uneven composition, which affects the welding quality.
A glass powder composed of tin oxide, phosphorus pentoxide, zinc oxide, lanthanum oxide, and organic carrier mainly composed of terpineol and ethyl cellulose were prepared by melting, water quenching and grinding.
The welding strength, interface stability, and acid and alkali resistance of the welding agent are improved, and the deviation of alkali metal dissolution and thermal expansion coefficients are reduced, and structural stability is enhanced.
Smart Images

Figure BDA0005202153930000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of welding, and in particular relates to a composition for welding ceramics and metals, and a preparation method and application thereof. Background Art
[0002] Medical micro feedthrough devices mainly involve a variety of categories such as electrophysiological monitoring feedthrough, ultrasound imaging feedthrough, implantable device signal feedthrough, etc., which are used in many key medical scenarios such as cardiovascular interventional treatment, neurosurgery monitoring, wearable medical device data transmission, etc. The feedthrough connector is a ceramic insulator and a metal wire welded into a whole at high temperature through metal melting.
[0003] For example, the publication number CN102824692A provides a feed-through connector for implantable medical devices, including a flange ring, an insulator, at least one signal probe, and a glass sealing body that fixes and hermetically seals the above structure. The glass sealing body contains SiO2 (about 60-80%), Al2O3 (about 5-15%), B2O3 (about 10-25%), Li2O (about 0-5%), Na2O (about 5-15%) and K2O (about 0-5%), and the content is all in mass percentage. This type of process has the following shortcomings:
[0004] (1) The above-mentioned traditional glass seal contains a large amount of alkali metal oxides (such as Na2O, Li2O, K2O). In some harsh chemical environments, alkali metal ions are easily dissolved by chemical reactions with external substances. For example, in the human physiological environment, acidic and alkaline substances in blood and tissue fluid may exchange with alkali metal ions, causing the glass structure to be destroyed;
[0005] (2) Although B2O3 can adjust the thermal expansion coefficient to a certain extent, it is difficult to accurately control the thermal expansion coefficient to match different materials (such as ceramics and metals) due to its large number and complexity of components;
[0006] (3) In terms of mechanical strength, due to the complex composition of traditional glass seals, microstructural defects may occur during the sealing process due to uneven distribution of components. For example, uneven distribution of alkali metal oxides may cause local loose structure, affecting the sealing quality.
[0007] In summary, the use of this glass component and formula will greatly reduce the practical value, and it is necessary to further optimize the composition and process to develop a feedthrough connector with good biocompatibility. Summary of the invention
[0008] The invention provides a composition for welding ceramics and metals, and a preparation method and application thereof.
[0009] The technical solution of the present invention is as follows:
[0010] The present invention provides a ceramic and metal welding composition, the composition is composed of glass powder and an organic carrier, the glass powder includes the following raw materials in percentage by weight:
[0011] Tin oxide 30%-40%, phosphorus pentoxide 20%-30%, zinc oxide 20%-30%, lanthanum oxide 1%-5%;
[0012] The particle size of the glass powder is 30-50 μm.
[0013] The weight ratio of the glass powder to the organic carrier is 6-8:2-4.
[0014] The organic carrier is terpineol and ethyl cellulose, and the weight ratio of terpineol to ethyl cellulose is 8-9:1-1.5.
[0015] The present invention also provides a method for preparing the ceramic-metal welding composition, comprising the following steps:
[0016] (1) mixing tin oxide, phosphorus pentoxide, zinc oxide, and lanthanum oxide, and then melting, water quenching, and grinding the mixture in sequence to obtain glass powder;
[0017] (2) The glass powder is mixed with an organic carrier consisting of pinene alcohol and ethyl cellulose, and ground to obtain a composite.
[0018] In the step (1), the melting temperature is 1000-1200° C. and the melting time is 2-3 hours.
[0019] In the step (1), the particle size of the glass powder is 30-50 μm.
[0020] The present invention also provides an application of the ceramic and metal welding composition prepared by the preparation method in welding agent.
[0021] Furthermore, the ceramic-metal welding composition is used to improve the welding strength, interface stability, acid and alkali resistance of the welding agent, reduce the dissolution of alkali metals, and reduce the deviation of thermal expansion coefficient.
[0022] Beneficial Effects
[0023] The present invention provides a composition for welding ceramics and metals, wherein the glass powder in the composition includes tin oxide, phosphorus pentoxide, zinc oxide, and lanthanum oxide, thereby enhancing structural stability. The composition is used as a welding agent to weld ceramics and metals, and has good welding strength, interface stability, acid and alkali resistance, less alkali metal dissolution, and small thermal expansion coefficient deviation. DETAILED DESCRIPTION
[0024] The following examples are intended to illustrate the present invention rather than to further limit the present invention.
[0025] The present invention provides a composition for welding ceramics and metals, the composition comprising glass powder and an organic carrier, the glass powder comprising the following raw materials in percentage by weight:
[0026] Tin oxide 30%-40%, phosphorus pentoxide 20%-30%, zinc oxide 20%-30%, lanthanum oxide 1%-5%;
[0027] The particle size of the glass powder is 30-50 μm. Glass powder within this particle size range can ensure good fluidity and have sufficient specific surface area, which is beneficial to subsequent welding.
[0028] Wherein, the weight ratio of glass powder to organic carrier is 6-8:2-4.
[0029] In addition, the organic carrier is terpineol and ethyl cellulose, wherein terpineol is used as an organic solvent and ethyl cellulose is used as a coupling agent, and the weight ratio of terpineol to ethyl cellulose is 8-9:1-1.5.
[0030] The present invention also provides a method for preparing the ceramic-metal welding composition, comprising the following steps:
[0031] (1) Tin oxide, phosphorus pentoxide, zinc oxide, and lanthanum oxide are mixed, and then melted, water-quenched, and ground to obtain glass powder.
[0032] Specifically, by mass percentage, 30%-40% of tin oxide, 20%-30% of phosphorus pentoxide, 20%-30% of zinc oxide, and 1%-5% of lanthanum oxide are mixed and then melted.
[0033] It should be noted that, in addition to the above raw materials, it may contain a small amount of other impurities or trace auxiliary ingredients.
[0034] Preferably, the melting temperature is 1000-1200° C. and the melting time is 2-3 h.
[0035] During the melting process, the atoms work together and "reshape" each other. After the melting is completed, water quenching is carried out, for example, with the help of a cooling rate exceeding 100°C / s, to obtain glass slag. The glass slag is ground and sieved to obtain glass powder of the target particle size.
[0036] Furthermore, the particle size of the glass powder is 30-50 μm to ensure the welding effect.
[0037] (2) The glass powder is mixed with an organic carrier consisting of pinene alcohol and ethyl cellulose, and ground to obtain a composite.
[0038] Preferably, the weight ratio of glass powder to organic carrier is 6-8:2-4.
[0039] Furthermore, the weight ratio of terpineol to ethyl cellulose is 8-9:1-1.5.
[0040] By adjusting the amount of glass powder, pinene alcohol, and ethyl cellulose added, the flexibility of operation is increased, and it can also better adapt to different practical application scenarios and material property requirements. In specific operations, the ratio of glass powder to organic carrier can be adjusted within an appropriate range according to actual conditions (such as requirements for the fluidity, drying speed, welding strength, and other properties of the composition).
[0041] For example, when there are high requirements for welding strength or the subsequent drying process needs to be carried out at a lower drying speed, the proportion of glass powder should be appropriately increased; when there are high requirements for the fluidity of the composition or the subsequent drying process needs to be carried out at a higher drying speed, the proportion of organic carrier should be appropriately increased.
[0042] Specifically, the mixture is fully ball-milled in a ball mill to obtain a uniform composition.
[0043] The invention also provides an application of the ceramic and metal welding composition in welding agent.
[0044] Specifically, the ceramic and metal welding composition is used to improve the welding strength, interface stability, and acid and alkali resistance of the welding agent.
[0045] The obtained composition is used as a welding agent for welding ceramics and metals. The specific welding process is as follows:
[0046] Step 1: Pre-treatment of ceramic insulators and platinum conductors
[0047] Select alumina ceramic insulators with an alumina content of ≥95%. According to actual application requirements, the outer diameter of the insulator is set in the range of 5-20mm and the length is controlled to be 10-50mm. Before use, place the ceramic insulator in an acetone solution and use ultrasonic cleaning technology for 10-15 minutes. Through ultrasonic cavitation, the surface oil and impurities are strongly removed, and then dried in an oven at 80-100℃ for 1-2 hours.
[0048] For platinum wire, high-quality products with a purity of ≥99.9% and a wire diameter of 0.3-1.5mm are selected. First, wipe it carefully with alcohol to remove surface stains, then place it in a hydrogen atmosphere and anneal it at 400-500℃ for 30-60min. With the synergistic effect of hydrogen reduction and thermal annealing, the internal stress is eliminated and its flexibility is significantly improved, laying a solid foundation for subsequent welding.
[0049] Step 2: Coating
[0050] The composition obtained by the present invention is coated on the welding part of the ceramic insulator, and the coating thickness is 0.2-0.3mm. The coating thickness of the welding end of the platinum wire within the length range of 2-5mm is 0.1-0.2mm, so as to ensure that the interface material is sufficient and uniform during welding. The coating operation can be achieved by screen printing technology (the mesh number of the screen is accurately controlled at 200-300 meshes).
[0051] The coating thickness refers to the thickness measured after the composition is coated and dried. Preferably, the drying temperature is 80-120° C. and the drying time is 30-90 min.
[0052] In this drying temperature range, the pinene alcohol in the organic vehicle can gradually volatilize, while the glass powder and other components will not undergo adverse changes due to excessively high temperatures. For example, if the temperature is too high, the glass powder may soften prematurely or the components in the organic vehicle may decompose, affecting the quality of the coating layer.
[0053] Regarding drying time, generally speaking, thicker coatings require longer drying time to ensure that the organic solvents are fully volatilized. At the same time, factors such as environmental humidity will also affect the drying time. If the environmental humidity is high, the drying time may need to be appropriately extended to ensure that the coating can be completely dried. In actual operation, the degree of drying can be preliminarily judged by observing the appearance of the coating. When the surface of the coating changes from wet to dry and has no obvious stickiness, it can be preliminarily judged that the drying is basically completed, but the final result is still subject to the thickness measurement result meeting the requirements.
[0054] Step 3: Pre-assembly
[0055] The ceramic insulator coated with the composition and the platinum wire are precisely docked so that the welding parts of the two are closely aligned and fixed with a professional clamp. The clamp pressure is precisely controlled at 0.4-0.6MPa to ensure that the gap between the ceramic insulator and the platinum wire is stably maintained at 0.05-0.1mm, creating ideal conditions for subsequent high-quality welding.
[0056] Step 4: Soldering
[0057] The pre-assembled weldment is placed steadily in a heating furnace, and the temperature is steadily increased from room temperature to 350-400°C at a heating rate of 5-8°C / min, and kept warm for 20-30 minutes; after the insulation is completed, the temperature is reduced to 200°C at a cooling rate of 3-5°C / min, and then naturally cooled to room temperature.
[0058] The heating parameters of the heating welding process must be strictly controlled. First, the heating rate must be consistent with the laws of heat conduction and melting dynamics between welds to avoid internal defects. Second, the holding temperature and time must be able to meet the energy required for atomic migration and chemical reactions to achieve atomic bonding between interfaces. Third, the cooling rate must be appropriate to control the “gradual” release of thermal stress and avoid cracks caused by uneven shrinkage due to sudden cooling. Finally, combined with natural cooling, residual stress can be slowly eliminated to stabilize the welded structure.
[0059] Example 1
[0060] (1) 40% tin oxide, 30% phosphorus pentoxide, 25% zinc oxide, and 5% lanthanum oxide were mixed by mass percentage and melted at 1100° C. for 2.5 hours;
[0061] After melting, water quenching is performed to obtain glass slag, which is then ground and sieved to obtain glass powder with a particle size of 30-50 μm.
[0062] (2) The glass powder and an organic carrier composed of terpineol and ethyl cellulose in a weight ratio of 9:1 were mixed in a weight ratio of 7:3, and the mixture was fully ball-milled to obtain a composite.
[0063] (3) Select an alumina ceramic insulator (alumina content ≥ 95%) with an outer diameter of 10 mm and a length of 30 mm, ultrasonically clean it in an acetone solution for 12 min, dry it in an oven at 90° C. for 1.5 h, and set it aside for use;
[0064] A platinum wire with a purity of 99.95% and a wire diameter of 0.5 mm was selected, wiped with alcohol, and annealed at 450° C. for 45 minutes in a hydrogen atmosphere before use.
[0065] (4) using a 250 mesh screen printing method to apply the composition to the welding part of the ceramic insulator, and after drying, the thickness is 0.25 mm;
[0066] The welding end of the platinum wire with a length of 3 mm was coated with the composition, and after drying, the thickness was 0.15 mm.
[0067] (5) The ceramic insulator and the platinum wire are preassembled and fixed with a clamp at 0.5 MPa so that the gap between the ceramic insulator and the platinum wire is 0.08 mm.
[0068] (6) The pre-assembled weldment is placed steadily in a heating furnace, and the temperature is steadily increased from room temperature to 380°C at a heating rate of 6°C / min, and kept at this temperature for 25 minutes. After the insulation is completed, the temperature is reduced to 200°C at a cooling rate of 4°C / min, and then naturally cooled to room temperature.
[0069] Example 2
[0070] (1) 35% tin oxide, 30% phosphorus pentoxide, 30% zinc oxide, and 5% lanthanum oxide were mixed by mass percentage and melted at 1100° C. for 2.5 hours;
[0071] After melting, water quenching is performed to obtain glass slag, which is then ground and sieved to obtain glass powder with a particle size of 30-50 μm.
[0072] (2) The glass powder and an organic carrier composed of terpineol and ethyl cellulose in a weight ratio of 9:1 were mixed in a weight ratio of 7:3, and the mixture was fully ball-milled to obtain a composite.
[0073] (3) Select an alumina ceramic insulator (alumina content ≥ 95%) with an outer diameter of 5 mm and a length of 10 mm, ultrasonically clean it in an acetone solution for 12 min, dry it in an oven at 90° C. for 1.5 h, and set it aside for use;
[0074] A platinum wire with a purity of 99.9% and a wire diameter of 0.3 mm was selected, wiped with alcohol, and annealed at 450° C. for 45 minutes in a hydrogen atmosphere before use.
[0075] (4) using a 250 mesh screen printing method to apply the composition to the welding part of the ceramic insulator, and after drying, the thickness is 0.25 mm;
[0076] The welding end of the platinum wire with a length of 3 mm was coated with the composition, and after drying, the thickness was 0.15 mm.
[0077] (5) The ceramic insulator and the platinum wire are preassembled and fixed with a clamp at 0.5 MPa so that the gap between the ceramic insulator and the platinum wire is 0.08 mm.
[0078] (6) The pre-assembled weldment is placed steadily in a heating furnace, and the temperature is steadily increased from room temperature to 380°C at a heating rate of 6°C / min, and kept at this temperature for 25 minutes. After the insulation is completed, the temperature is reduced to 200°C at a cooling rate of 4°C / min, and then naturally cooled to room temperature.
[0079] Example 3
[0080] (1) 40% tin oxide, 25% phosphorus pentoxide, 30% zinc oxide, and 5% lanthanum oxide were mixed by mass percentage and melted at 1100° C. for 2.5 hours;
[0081] After melting, water quenching is performed to obtain glass slag, which is then ground and sieved to obtain glass powder with a particle size of 30-50 μm.
[0082] (2) The glass powder and an organic carrier composed of terpineol and ethyl cellulose in a weight ratio of 9:1 were mixed in a weight ratio of 7:3, and the mixture was fully ball-milled to obtain a composite.
[0083] (3) Select an alumina ceramic insulator (alumina content ≥ 95%) with an outer diameter of 10 mm and a length of 30 mm, ultrasonically clean it in an acetone solution for 12 min, dry it in an oven at 90° C. for 1.5 h, and set it aside for use;
[0084] A platinum wire with a purity of 99.95% and a wire diameter of 0.5 mm was selected, wiped with alcohol, and annealed at 450° C. for 45 minutes in a hydrogen atmosphere before use.
[0085] (4) using a 250 mesh screen printing method to apply the composition to the welding part of the ceramic insulator, and after drying, the thickness is 0.25 mm;
[0086] The welding end of the platinum wire with a length of 3 mm was coated with the composition, and after drying, the thickness was 0.15 mm.
[0087] (5) The ceramic insulator and the platinum wire are preassembled and fixed with a clamp at 0.5 MPa so that the gap between the ceramic insulator and the platinum wire is 0.08 mm.
[0088] (6) The pre-assembled weldment is placed steadily in a heating furnace, and the temperature is steadily increased from room temperature to 380°C at a heating rate of 6°C / min, and kept at this temperature for 25 minutes. After the insulation is completed, the temperature is reduced to 200°C at a cooling rate of 4°C / min, and then naturally cooled to room temperature.
[0089] Comparative Example 1
[0090] Compared with Example 1, lanthanum oxide is not added in step (1), and the remaining operations, raw material types and addition amounts are consistent with those in Example 1.
[0091] Comparative Example 2
[0092] The raw materials of publication number CN102824692A are used for preparation, specifically:
[0093] (1) 70% SiO2, 10% Al2O3, 10% B2O3, 3% Li2O, 5% Na2O and 2% K2O were mixed by mass percentage and melted at 1100°C for 2.5h;
[0094] After melting, water quenching is performed to obtain glass slag, which is then ground and sieved to obtain glass powder with a particle size of 30-50 μm.
[0095] (2) The glass powder and an organic carrier composed of terpineol and ethyl cellulose in a weight ratio of 9:1 were mixed in a weight ratio of 7:3, and the mixture was fully ball-milled to obtain a composite.
[0096] (3) Select an alumina ceramic insulator (alumina content ≥ 95%) with an outer diameter of 10 mm and a length of 30 mm, ultrasonically clean it in an acetone solution for 12 min, dry it in an oven at 90° C. for 1.5 h, and set it aside for use;
[0097] A platinum wire with a purity of 99.95% and a wire diameter of 0.5 mm was selected, wiped with alcohol, and annealed at 450° C. for 45 minutes in a hydrogen atmosphere before use.
[0098] (4) using a 250 mesh screen printing method to apply the composition to the welding part of the ceramic insulator, and after drying, the thickness is 0.25 mm;
[0099] The welding end of the platinum wire with a length of 3 mm was coated with the composition, and after drying, the thickness was 0.15 mm.
[0100] (5) The ceramic insulator and the platinum wire are preassembled and fixed with a clamp at 0.5 MPa so that the gap between the ceramic insulator and the platinum wire is 0.08 mm.
[0101] (6) The pre-assembled weldment is placed steadily in a heating furnace, and the temperature is steadily increased from room temperature to 380°C at a heating rate of 6°C / min, and kept at this temperature for 25 minutes. After the insulation is completed, the temperature is reduced to 200°C at a cooling rate of 4°C / min, and then naturally cooled to room temperature.
[0102] Performance Testing
[0103] 1. Welding strength test
[0104] According to GB / T 2651-2008 “Tensile test method for welded joints”, the welding strength of the weldments of Examples 1-3 and Comparative Examples 1-2 was tested.
[0105] 2. Interface stability test
[0106] The test is carried out in accordance with GB / T 2654-2008 "Welding Joint Hardness Test Method" and combined with a customized electrical load and temperature cycle test procedure. First, before the electrical load and temperature cycle test, according to the method specified in GB / T 2654-2008, use appropriate hardness testing equipment (such as Vickers hardness tester or Rockwell hardness tester) to select multiple test points at different positions of the welding joint (including the ceramic and glass interface, the glass and metal interface, and the parent material area away from the interface), measure their initial hardness values, and record the hardness distribution. Then, the weldment is placed in a specially designed test equipment for a simulated 500-hour electrical load and -30℃ to 150℃ temperature cycle test. During the test, the parameters of the electrical load (such as current, voltage, frequency, etc.) are controlled within a specific range to simulate the electrical signal transmission in actual working conditions; the temperature cycle uses a precise temperature control system to ensure that the temperature change rate, low temperature holding time, high temperature holding time, etc. meet the set requirements. After the test, measure the hardness value at the same test point again according to GB / T 2654-2008 standard, and compare the change of hardness value before and after the test. If the change of hardness value is within the allowable error range, and the hardness distribution is still uniform, and no obvious cracks, desoldering and other defects are found in the welding interface through microscope observation, and the signal transmission is stable during the electrical load test (real-time monitoring by the signal detection equipment connected to the weldment), then the interface stability is judged to be good.
[0107] In Example 1, the hardness value fluctuation range of each test point of the welding joint before the test is between 60-70HV. After 500 hours of testing, the hardness value fluctuation range is between 58-72HV, and the deviation of 58-72HV or 60-70HV is within ±2HV. There are no obvious defects in the interface under the microscope, the signal transmission is stable, and the interface is determined to be stable. The hardness value range of Example 2 is 53-67HV, and the deviation range is ±2HV. Although the composition has changed, the overall interface stability can still ensure that the hardness fluctuates within a reasonable range. The hardness value range of Example 3 is 53-67HV, and the deviation range is ±2HV. Although the composition has changed, the overall interface stability can still ensure that the hardness fluctuates within a reasonable range. The hardness value range of Comparative Example 1 is 45-65HV, and the deviation range is ±5HV. After testing, due to the lack of lanthanum oxide optimization of the structure, the hardness changes relatively greatly, and hardness mutations may occur in local areas, which reflects the poor interface stability. The hardness value range of comparative example 2 is 30-60HV, and the deviation range is ±10HV. During the simulation test, due to the structural instability caused by factors such as alkali metal oxides, the hardness changes significantly under thermal stress and electrical stress, and local softening or hardening may occur. At the same time, microscopic observation shows that there are obvious cracks and signs of desoldering at the welding interface, and the signal transmission is also unstable, indicating that the interface stability is poor.
[0108] 3. Alkali metal dissolution test
[0109] The alkali metal dissolution test is carried out according to the relevant principles in GB / T 1549-2008 "Chemical Analysis Methods for Fiber Glass". First, accurately prepare an immersion solution that simulates the human body environment, control the solution's composition (such as simulating the main ion components in blood and tissue fluid), pH value, osmotic pressure and other parameters, and make it as close to the real human physiological environment as possible. The welded weldment is completely immersed in the immersion solution and soaked at a specific temperature (such as 37°C, simulating human body temperature) for 30 days. After the immersion, the amount of alkali metal dissolution is determined by atomic absorption spectroscopy (AAS). The specific operation is as follows: Use an AAS instrument to first dilute and pretreat the immersion solution appropriately to eliminate the interference of other components in the detection of alkali metal elements. Then, according to the characteristic absorption wavelengths of different alkali metal elements (such as Na, K, etc.), they are detected separately, and the concentration of alkali metal ions in the immersion solution is calculated by comparing with the absorbance of the standard solution, and then the alkali metal dissolution amount (ppm) is obtained. For example, in Comparative Example 2, after detecting Na in the immersion solution, + The concentration is 30ppm, K + The concentration is 25ppm, and the total alkali metal dissolution exceeds 50ppm. In Examples 1-3, Na + The concentrations were all below 0.5ppm, K + The concentration is less than 0.5ppm and the total alkali metal dissolution is less than 1ppm.
[0110] 4. Thermal expansion coefficient deviation test
[0111] In the range of -50°C to 200°C, the thermal expansion coefficient deviations of the weldments of Examples 1-3 and Comparative Examples 1-2 were detected.
[0112] 5. Acid and alkali resistance test
[0113] For the acid-base test simulating the human physiological environment (immersion in a pH 2-12 solution for 7 days), firstly, an acid solution with a pH value of 2 and an alkaline solution with a pH value of 12 are accurately prepared according to the standard requirements, and a precision pH meter is used for calibration and measurement to ensure the accuracy of the solution pH value. The weldment is immersed in the acid solution and the alkaline solution respectively, and immersed at a constant temperature (such as 25°C) for 7 days. After the immersion is completed, the weldment is taken out, the surface is gently rinsed with deionized water to remove the residual solution, and then dried in a drying oven at an appropriate temperature (such as 60°C) to constant weight. The weight loss rate is calculated by measuring the mass change of the weldment before and after immersion, and the formula is: weight loss rate = [(mass before immersion - mass after immersion) / mass before immersion] × 100%. At the same time, the erosion of the weldment surface is observed using a microscope, and whether there are pits, cracks, gloss changes, etc.
[0114] For example, in Example 1, the weight loss rate after immersion in a solution with a pH value of 2 is 0.03%, the weight loss rate after immersion in a solution with a pH value of 12 is 0.05%, the total weight loss rate is less than 0.1%, and there are no obvious potholes and erosion marks on the surface, and the surface is smooth; while in Comparative Example 2, the weight loss rate after immersion in a solution with a pH value of 2 is 0.2%, the weight loss rate after immersion in a solution with a pH value of 12 is 0.4%, the total weight loss rate exceeds 0.5%, there are obvious erosion potholes on the surface, and the glossiness is significantly reduced.
[0115] The above test results are organized into a table, see Table 1 for details.
[0116] Table 1 Test comparison
[0117]
[0118] As can be seen from Table 1, compared with Comparative Example 1 and Comparative Example 2, the compositions obtained by using the raw materials and preparation methods of Examples 1-3, and coated on ceramic and platinum wires, have good welding strength, interface stability, acid and alkali resistance, less alkali metal dissolution, and small thermal expansion coefficient deviation.
[0119] Besides, the coating thickness in welding process and the working parameters of heating furnace during heating welding were compared.
[0120] When the coating thickness is changed, specifically, compared with Example 1, in step (4), the composition is applied to the welding part of the ceramic insulator, and after drying, the thickness is 0.35 mm; the composition is applied to the welding end of the platinum wire for 3 mm in length, and after drying, the thickness is 0.25 mm. The remaining operations, raw material types, and addition amounts are consistent with Example 1.
[0121] The welding strength of the weldment is 16N / mm 2 A small number of tiny cracks appeared on the welding interface, the signal transmission had slight fluctuations, and the performance was not as good as Example 1.
[0122] When heating and welding, the working parameters of the heating furnace are changed. Specifically, compared with Example 1, in step (6), the pre-assembled weldment is steadily placed in the heating furnace, and the temperature is steadily increased from room temperature to 380°C at a heating rate of 10°C / min, and kept warm for 15 minutes; after the insulation is completed, the temperature is reduced to 200°C at a cooling rate of 6°C / min, and then naturally cooled to room temperature.
[0123] The welding strength of the weldment is 15N / mm 2 , local desoldering occurs at the welding interface, and the performance is not as good as that of Example 1.
Claims
1. A ceramic and metal welding composition, characterized in that: The composition is composed of glass powder and an organic carrier, wherein the glass powder includes the following raw materials in percentage by weight: Tin oxide 30%-40%, phosphorus pentoxide 20%-30%, zinc oxide 20%-30%, lanthanum oxide 1%-5%; The particle size of the glass powder is 30-50 μm.
2. The ceramic-metal welding composition according to claim 1, characterized in that: The weight ratio of the glass powder to the organic carrier is 6-8:2-4.
3. The ceramic-metal welding composition according to claim 1, characterized in that: The organic carrier is terpineol and ethyl cellulose, and the weight ratio of terpineol to ethyl cellulose is 8-9:1-1.
5.
4. A method for preparing a ceramic-metal welding composition according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing tin oxide, phosphorus pentoxide, zinc oxide, and lanthanum oxide, and then melting, water quenching, and grinding the mixture in sequence to obtain glass powder; (2) The glass powder is mixed with an organic carrier consisting of pinene alcohol and ethyl cellulose, and ground to obtain a composite.
5. The method for preparing a ceramic-metal welding composition according to claim 4, characterized in that: In the step (1), the melting temperature is 1000-1200° C. and the melting time is 2-3 hours.
6. The method for preparing a composition for welding ceramics to metals according to claim 4, characterized in that: In the step (1), the particle size of the glass powder is 30-50 μm.
7. Use of the ceramic-metal welding composition according to any one of claims 1 to 3 or the ceramic-metal welding composition prepared by the preparation method according to any one of claims 4 to 6 in a welding agent.
8. The use according to claim 7, characterized in that: The ceramic and metal welding composition is used to improve the welding strength, interface stability, acid and alkali resistance of the welding agent, reduce the dissolution of alkali metals, and reduce the deviation of thermal expansion coefficient.
Citation Information
Patent Citations
Feed-through connector for implantable medical device and manufacturing method
CN102824692A
No-lead RE doped sealing glass powder with low smelting point and its production process
CN101066840A
Phosphorus-bismuth non-lead low-melting point glass
CN101973708A
Sealing glass and sealing composite material
CN103025677A
Feed-through
CN107001117A